2016
DOI: 10.1111/jav.01055
|View full text |Cite
|
Sign up to set email alerts
|

Winter territory prospecting is associated with life‐history stage but not activity in a passerine

Abstract: Finding a high quality territory is essential for many animals to reproduce successfully. Despite its importance for fitness, we know little about the process of territory prospecting in wild birds, and whether individual traits and behaviours, such as personality, co-vary with territory prospecting. Here, we use long-term data from a wild, insular house sparrow Passer domesticus population to test three hypotheses about territory fidelity and prospecting: 1) house sparrows show high territory fidelity between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…The datasets from van Overveld et al and Kralj‐Fišer et al present the original published data from the paper plus additional unpublished data. The dataset of Lundy sparrow project (unpublished data) present data partially published in Sánchez‐Tójar et al .…”
Section: Methodsmentioning
confidence: 99%
“…The datasets from van Overveld et al and Kralj‐Fišer et al present the original published data from the paper plus additional unpublished data. The dataset of Lundy sparrow project (unpublished data) present data partially published in Sánchez‐Tójar et al .…”
Section: Methodsmentioning
confidence: 99%
“…The novel environment was a domed tent containing two artificial bamboo‐cane trees (Appendix S1: Fig. S1b, described in Sánchez‐Tójar et al ., ). Birds were observed for 5 min through a mesh triangle (approximately 5 × 5 × 7 cm).…”
Section: Methodsmentioning
confidence: 97%
“…Nestlings were placed in a circular arena marked with a grid pattern and surrounded by a wall (Appendix S1: Fig. S1c, described in Sánchez‐Tójar et al ., ). We video‐recorded the nestlings’ activity and recorded the total number of squares a nestling crossed in 30 seconds.…”
Section: Methodsmentioning
confidence: 97%
“…Taking into account that only the manipulated parents of the year before had a transponder and first year breeders which did not have a transponder were also around, the true degree of competition was likely higher. It is known from other passerine species that birds also under "natural" conditions exhibit prospecting behaviour, that is, inspecting multiple nesting sites before and during breeding (Doligez, Cadet, Danchin, & Boulinier, 2003;Doligez, Pärt, & Danchin, 2004;Pärt & Doligez, 2003;Sánchez-Tójar et al, 2017). For House sparrows (Passer Domesticus), it was shown that experienced adult breeders prospected very little, likely because they hold on to the same territories year round (Sánchez-Tójar et al, 2017).…”
Section: Was Competition For Breeding Boxes Successfully Induced?mentioning
confidence: 99%
“…It is known from other passerine species that birds also under "natural" conditions exhibit prospecting behaviour, that is, inspecting multiple nesting sites before and during breeding (Doligez, Cadet, Danchin, & Boulinier, 2003;Doligez, Pärt, & Danchin, 2004;Pärt & Doligez, 2003;Sánchez-Tójar et al, 2017). For House sparrows (Passer Domesticus), it was shown that experienced adult breeders prospected very little, likely because they hold on to the same territories year round (Sánchez-Tójar et al, 2017). The same may hold for the territorial Great tit (Andreu & Barba, 2006;Tinbergen, 2005) under "natural" levels of competition for nest boxes.…”
Section: Was Competition For Breeding Boxes Successfully Induced?mentioning
confidence: 99%